(3Sdhc GdeGdc aj JOHjQ GdeeGdcs - (3CMeO Hf CHj GdQHjY , TgGH GdOjf CHh GdYHGS CMeO Hf eMeO Hf CHj GdQHjY, GHf CHj GdQHjY,J (B227 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf ai CMSf Jbhje s
(3BNQgG (B:s
(3hEP bO hajfG HeG CQOfG JdNjUg hJTLjQg ai gPG GdcJGHq s
(3HgG CTcGd JhVjMjIs
(3HgG fXGe GdJYbjHIs
(3fSNI NRGFfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B101s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1000s
Keywords: (3GdadSaI hGdefWbs